A PDCA Eight-Step Approach to Misrun Defect Reduction in Hatchback Gasoline Car Piston Castings - Muhammad Prasha Risfi Silitonga; Chika Mutiara Syafira; Riyan Setiyadi; Hilmana Radhia Putera (Politeknik Siber Cerdika Internasional, 2026)
Background:Misrun defects represent a critical quality issue in metal casting processes, particularly in gasoline piston manufacturing, as they lead to material waste, reduced productivity, and increased production costs. At PT XYZ, misrun defects constituted the highest proportion of total defects in 2024, indicating the need for systematic quality improvement. Objective:This study aims to analyze the root causes of misrun defects in hatchback gasoline car piston castings and evaluate the effectiveness of corrective actions using the PDCA Eight-Step strategy. Method:A qualitative–quantitative approach was employed through the application of the PDCA (Plan–Do–Check–Action) cycle with an Eight-Step problem-solving framework. Root cause analysis was conducted using fishbone diagrams and the 5 Why method. Corrective actions focused on mold design, cooling inspection procedures, and gas flow optimization. Results:The findings show that misrun defects accounted for 52.56% of total defects, with piston type X contributing 9.84% of the overall misrun rate. After implementing corrective measures—namely additional and repositioned gas vents, standardized cooling mold inspections, and modified argon gas spray direction—the misrun defect rate was reduced to 5.16%. This represents a 47.5% reduction, exceeding the company’s quality improvement target of 40%. Conclusion:The PDCA Eight-Step strategy proved effective in significantly reducing misrun defects and improving casting quality. This study provides a practical and replicable framework for defect reduction in precision casting industries while reinforcing the theoretical relevance of structured PDCA-based quality improvement in manufacturing systems.